Clinical outcomes of breast cancer patients treated in phase I clinical trials at University of Colorado Cancer Center. (16th October 2020) - Weiss, Jennifer A.; Nicklawsky, Andrew; Kagihara, Jodi A.; Gao, Dexiang; Fisher, Christine; Elias, Anthony; Borges, Virginia F.; Kabos, Peter; Davis, Sarah L.; Leong, Stephen; Eckhardt, Sue Gail; Diamond, Jennifer R.
Abstract: Patients with metastatic breast cancer (MBC) refractory to standard of care therapies have a poor prognosis. The purpose of this study was to assess patient characteristics and clinical outcomes for patients with MBC treated on phase I clinical trials. We performed a retrospective review of all patients with MBC who were enrolled in phase I clinical trials at the University of Colorado Cancer Center from January 2012 to June 2018. A total of 208 patients were identified. Patients had a mean age of 57 years and received on average 2.1 (range 0‐10) prior lines of chemotherapy. The majority of patients had hormone receptor‐positive/HER2‐negative breast cancer (58.6%) and 30.3% had triple‐negative breast cancer. The median progression free survival (PFS) was 2.8 months (95% CI, 2.3‐3.9) and median overall survival (OS) was 11.5 months (95% CI, 9.6‐13.2). Independent factors associated with longer PFS in multivariable analysis were treatment in a breast cancer‐selective trial or cohort ( p  = 0.016), age >50 years ( p  = 0.002), and ≤2 prior lines of chemotherapy in the metastatic setting ( p  = 0.025). Phase I clinical trials remain a valuable option for select patients with MBC and enrollment should be encouraged when available. Abstract : We performed a retrospective review of all patients with metastatic breast cancer (MBC) who were enrolled in phase I clinical trials at the University of Colorado Cancer Center. Independent factors associated with longer PFS in multivariable analysis were treatment in a breast cancer‐selective trial or cohort, age >50 years, and ≤2 prior lines of chemotherapy in the metastatic setting. Phase I clinical trials remain a valuable option for selecting patients with MBC and enrollment should be encouraged when available.